Modern micro-economics theory and application - Choudhury, Kalyanjit Roy (New Delhi Dominant, 2001)
Modern micro-economics Theory and application is in three volumes.There three volumes covers the topics of-Theory of consumer behaviour,production costs, market forms,factor pricing linear programming international trade,welfare economics.
Keywords: Microeconomics; Equilibrium (Economics); Economic development